دراسة الفيضان في نهر السن - غطفان عمَّار (Tishreen University, 2019)
تهدف الدراسة إلى تحديد الفيضانات الأعظمية في نهر السن، التي يمكن أن تحدث خلال فترات زمنية مختلفة، واقتراح الحلول المناسبة لدرء هذه الفيضانات، وبسبب عدم وجود معلومات كافية عن تدفقات هذا النهر،  وتدفقات روافده تمَّ استخدام المعادلة المنطقية لحساب التدفقات الأعظمية، حيث اعتمدنا على بيانات الهطل المطري لثلاث محطات رصد جوي، منتشرة ضمن حوضه الساكب وعلى محيطه، وامتدت فترة القياس فيها ما بين 32 و34 عاماً. توصلت الدراسة إلى أنَّ الفيضانات التي يمكن حدوثها لفترات زمنية مختلفة كبيرة جداً، وخاصةً عند التقاء النهر مع رافده الرئيسي أبو بعرة، وأنَّ المجرى الموجود حالياً لا يمكنه استيعاب هذه الفيضانات، لذلك لابد من تنظيم مجرى النهر بشكلٍ جيد من أجل حماية المناطق السكنية، والأراضي الزراعية المجاورة من الغرق. كما أنَّه يجب إنشاء محطات قياس في أمكنة مختلفة من النهر، واستمرار قياس التدفقات، من أجل إمكانية التنبؤ عن الفيضانات، التي يمكن أن تحدث بشكل أكثر دقةً. This study aims to specify the maximum floods that can occur in Al-sen river in different periods of time. It also aims to suggest the appropriate solution to avert these floods. Since there is not enough information about the flows of this river and its tributaries, the logical equation is used to account for the maximum floods, where we relied on the data of rainfall at three weather forecast stations، which can be found in its pool and on its periphery; the duration of measurement ranged from 32 to 34 years. The study concludes that the floods that may happen over different periods of time are very big, especially when the river and its main tributary Abo Baira converge. It also concludes that the present river cannot contain these floods, so it's necessary to maintain the river bed in a good way to protect the nearby residential and agricultural areas from flooding. In addition, it is essential to set up stations measuring the flood in specific places of the river and continue measuring these floods, which enable us to predict floods, which may happen more accurately.